Pre-Anesthesia Extracorporeal Membrane Oxygenation in Two Lung Transplant Recipients with Severe Pulmonary Hypertension - Liu Minqiang; Gao Hong; Chen Jingyu; Wang Yanjuan; Xu Bo; Wang Guilong; Wu Qiang; Hu Chunxiao (Case Reports in Medicine)
Extracorporeal membrane oxygenation (ECMO) is a widely used cardiopulmonary support method that is usually implemented after anesthesia during the period of lung transplantation (LTx). In severe pulmonary arterial hypertension (PAH) patients, however, anesthesia induction is a high-risk phase and can result in severe cardiorespiratory failure. Herein, we describe two severe PAH patients who received ECMO support before anesthesia and whose preoperative evaluations indicated that the risk was too high to safely survive the anesthesia induction period before LTx. The strategy was successful, and in both patients, hemodynamics was stable and no ECMO-related complications occurred.